Cell-cell contact mediated signalling — no fear of contact - Schmidmaier, R.; Baumann, P.; Meinhardt, G. (Experimental Oncology, 2006)
Cancer research with sole focus on the cancer cell and possibly growth factors cannot faithfully reproduce the environmental interaction, such as adhesion of tumor cells to e.g. stromal cells, which may determine the response of these tumors to therapy. Methodologically cell adhesion studies are often difficult since complete but careful detachment is the prerequisite for most signal transduction assays. We describe for the first time an alternative method for the co-incubation of multiple myeloma cells on long term primary bone marrow stromal cultures using the bone marrow stromal cell line HS-5. The methods are precisely described, advantages and disadvantages are discussed, and troubleshooting advises are given.